Radiographic and anatomic investigation on the prevalence of biﬁd mandibular canals in cone beam computed tomography scans - C. Casagrande; S. G. Orestes; A. D. Schroder; A. A. De-Lima; A. Franco; I. Makeeva; Â. Fernandes (Сеченовский вестник, 2018)
Background. Knowing the radiologic anatomy of the mandibular canal is essential to perform optimal anesthetic techniques in dentistry, especially in endodontic and surgical procedures. Biﬁd mandibular canals ﬁgure as anatomic variations that may hamper dental anesthesia and lead to surgical accidents.Objective. This study aims to investigate the prevalence of biﬁd mandibular canals in cone beam computed tomography (CBCT) images of patients under dental treatment.Material and methods. The sample consisted of 700 patients (448 females and 252 males) under dental treatment. CBCT images taken from each patient for dental treatment purposes were analyzed retrospectively in order to search for biﬁd mandibular canals. The detected biﬁd mandibular canals were classiﬁed according to their morphological arrangement and the prevalence of this anatomic variation was tested for association with patients’ sex using Pearson’s Chi-square test (2).Results. The prevalence rate of biﬁd mandibular canals reached 2% (n=14). Mandibular canals with an additional bifurcation towards the anterior region of the mandibular ramus were the most prevalent (100%). Lack of statistical association was observed between the occurrence of biﬁd mandibular canals and patients’ sex ( p >0.05).Conclusion. Despite uncommon, biﬁd mandibular canals may occur. Dentists must be aware of this anatomic variation to perform safely and optimally in the clinical routine.